The Mobility of Silver Nanoparticles and Silver Ions in the Soil‐Plant System. Issue 6 (1st November 2019) - Saleeb, Nadir; Gooneratne, Ravi; Cavanagh, Jo; Bunt, Craig; Hossain, A. K. M. Mofasser; Gaw, Sally; Robinson, Brett
Abstract : The widespread use of silver nanoparticles (AgNPs) as a bactericide will ultimately result in their increased concentration in soils. We sought to determine the likely mobility, toxicity, and plant uptake of Ag applied to soil as either AgNPs or Ag + . We measured the solubility, toxicity, and plant uptake of both AgNPs and Ag + in an immature Pallic soil, a Templeton loamy silt (pH = 5.1), and a granular silt loam (pH = 6.0). The sorption of AgNPs by the test soils was significantly greater than Ag +, and both moieties were more strongly sorbed at lower concentrations and higher pH values. Between pH 4 and 8, distribution coefficient ( K D ) values increased from <10 up to ∼500 L kg −1 for Ag +, and from 100 to 10, 000 L kg −1 for AgNPs. There was strong evidence that our citrate‐coated AgNPs were transformed into Ag + during the course of the plant growth experiments, and plant responses were similar for both the Ag + and AgNP treatments. Soil concentrations >100 mg kg −1 significantly reduced the biomass of Lolium perenne L. and resulted in foliar concentrations of up to 10 mg kg −1 dry matter. At a soil concentration of 70 mg kg −1, silverbeet [ Beta vulgaris L. ssp. maritima (L.) Arcang.] and spinach ( Spinacia oleracea L.) accumulated 5 to 10 mg Ag kg −1, which may present a human health risk. Regarding citrate‐coated AgNPs, the environmental impact of release is largely determined by the equivalent mass concentration of Ag +, into which they will ultimately transform. Given the widespread interest in AgNPs, there is limited knowledge on the behavior of Ag + in soil and this should be the subject of future research. Core Ideas: Citrate‐coated Ag nanoparticles had greater soil sorption than Ag + . Sorption of both Ag nanoparticles and Ag + increased at higher pH. Silver nanoparticles are ultimately unstable and transform to Ag + . Phytotoxicity occurs at soil Ag concentrations >100 mg kg −1 . Silver uptake by spinach and silverbeet may present a human health risk.